Capture Hi-C identifies a novel causal gene, IL20RA, in the pan-autoimmune genetic susceptibility region 6q23. Issue 1 (December 2016) - McGovern, Amanda; Schoenfelder, Stefan; Martin, Paul; Massey, Jonathan; Duffus, Kate; Plant, Darren; Yarwood, Annie; Pratt, Arthur; Anderson, Amy; Isaacs, John; Diboll, Julie; Thalayasingam, Nishanthi; et al.
Abstract Background The identification of causal genes from genome-wide association studies (GWAS) is the next important step for the translation of genetic findings into biologically meaningful mechanisms of disease and potential therapeutic targets. Using novel chromatin interaction detection techniques and allele specific assays in T and B cell lines, we provide compelling evidence that redefines causal genes at the 6q23 locus, one of the most important loci that confers autoimmunity risk. Results Although the function of disease-associated non-coding single nucleotide polymorphisms (SNPs) at 6q23 is unknown, the association is generally assigned toTNFAIP3, the closest gene. However, the DNA fragment containing the associated SNPs interacts through chromatin looping not only withTNFAIP3, but also withIL20RA, located 680 kb upstream. The risk allele of the most likely causal SNP, rs6927172, is correlated with both a higher frequency of interactions and increased expression ofIL20RA, along with a stronger binding of both the NFκB transcription factor and chromatin marks characteristic of active enhancers in T-cells. Conclusions Our results highlight the importance of gene assignment for translating GWAS findings into biologically meaningful mechanisms of disease and potential therapeutic targets; indeed, monoclonal antibody therapy targeting IL-20 is effective in the treatment of rheumatoid arthritis and psoriasis, both with strong GWAS associations to this region.